2012
DOI: 10.1111/j.1365-3059.2012.02628.x
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiadiazole‐primed defence responses and enhanced differential expression of defence genes in Vitis vinifera infected with biotrophic pathogens Erysiphe necator and Plasmopara viticola

Abstract: Benzothiadiazole (BTH), a salicylic acid analogue, strengthens plant defence mechanisms against a broad spectrum of pathogens. The role of pre-treatment with BTH in enhancing resistance against infection with various isolates of downy and powdery mildews (Plasmopara viticola and Erysiphe necator) was investigated in grapevine leaves. Tools were developed to better assess the defence status of the plant. In compatible interactions amongst a set of 19 genes, more than 57AE2% of differentiated transcripts from P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
74
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 35 publications
13
74
0
3
Order By: Relevance
“…An additional file shows the origin of the sequences and/or references used to find new candidate genes involved in grapevine defenses (Additional file 1). The strategy combines two approaches : the first was based on the comparison of new grapevine genomic data with known grapevine sequences previously selected from pathogen-related studies to which were added genes deployed in two recently developed molecular diagnostic tools (“grapevine - qPFD”, patent INRA FR 1055042/WO/2011/161388, CT/FR2011/051470 - INRA Angers - Brisset MN, [38] and “BioMolChem” chip, [26]). The sequences used in RT-qPCR were blasted against the most recent Vitis vinifera sequences (taxid = 29,760, [41]) using the Blast resource from the National Center for Biotechnology Information (https://blast.ncbi.nlm.nih.gov/Blast.cgi).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional file shows the origin of the sequences and/or references used to find new candidate genes involved in grapevine defenses (Additional file 1). The strategy combines two approaches : the first was based on the comparison of new grapevine genomic data with known grapevine sequences previously selected from pathogen-related studies to which were added genes deployed in two recently developed molecular diagnostic tools (“grapevine - qPFD”, patent INRA FR 1055042/WO/2011/161388, CT/FR2011/051470 - INRA Angers - Brisset MN, [38] and “BioMolChem” chip, [26]). The sequences used in RT-qPCR were blasted against the most recent Vitis vinifera sequences (taxid = 29,760, [41]) using the Blast resource from the National Center for Biotechnology Information (https://blast.ncbi.nlm.nih.gov/Blast.cgi).…”
Section: Resultsmentioning
confidence: 99%
“…As the expected action of these potentially eliciting products is rather preventive than curative and because preliminary studies [26] showed that the pathogen diverts the plant metabolism in its favor and particular by blocking the deployment of its defenses, we chose a sampling protocol rather early in the season when the period of grapevine sensitivity against downy mildew is the strongest than later after the pathogen inoculation or once the epidemic is in place at a time when there was no real point in tracking the defense status of the vine. The grapevine defense reaction was analyzed 48 h after a second elicitor treatment applied in the vineyard.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on literature, four agents for which the ability to induce plant defence mechanisms has been previously demonstrated were used here as positive "PDE controls": Bion 50WG®, BABA, Chitosan and methyl jasmonate (MeJA) (Amborabe et al 2004 ;Azami-Sardooei et al 2013 ;Dufour et al 2013 ;Eyre et al 2006 ;Zhu and Tian 2012 ). In addition to those "PDE controls", the protection efficacy against of seven potential PDE were investigated (coded A to G; Table 1 ).…”
Section: Leaf Treatments With Productsmentioning
confidence: 99%
“…Among available biocontrol strategies, the induction of resistant mechanisms, notably through the application of plant defence elicitors (PDE), represents a promising alternative to chemical fungicides (Ballester et al 2011 ). PDE can be defined as natural or synthetic compounds with no direct antifungal activity which, by mimicking natural signalling compounds, induce defence mechanisms in plants, in turn resulting in enhanced resistance to pests and pathogens upon attack (Fu and Dong 2013 ;Dufour et al 2013 ). Alternatively, some compounds do not immediately trigger plant defence mechanisms but provide resistance through a faster and/or stronger induction of defence mechanisms following pathogen and pest infection.…”
Section: Introductionmentioning
confidence: 99%